Perbedaan Indeks Massa Tubuh Sebelum Pengobatan Dan Sesudah Pengobatan Pada Pasien Tuberkulosis Paru Di Balai Besar Kesehatan Paru Masyarakat Surakarta - AL HUDA, Imam (2015)
Background: Tuberculosis is a major health problem in the world. Pulmonary tuberculosis is the second leading cause of death due to infectious disease after AIDS. Nutritional status of patients with pulmonary tuberculosis were significantly lower than healthy people. Mycobacterium tuberculosis infection causes a decreased food intake and malabsorbtion of nutrients. Malnutrition in pulmonary tuberculosis will worsen the course of the disease and affects the prognosis of treatment and mortality. Purpose: To determine differences in Body Massa Index (BMI) before treatment and after treatment in patients with pulmonary tuberculosis at the Balai Besar Kesehatan Paru Masyarakat Surakarta. Method: Analytic observasional study with cross sectional approach. Sample retrieved from medical records of 2013 in BBKPM Surakarta with purposive sampling technique. The data were analyzed by Paired t test in SPSS for Windows. Result: There was 216 pulmonary TB patients with a BMI < 17, totaling 52 Samples , patients with a BMI between 17.0-18.4 totaling 41 samples , patients with a BMI between 18.25-25.0 totaling 108 samples , patients with a BMI of 25,1-27.0 amounted to 8 samples , and with a BMI > 27 amounted to 7 samples . After the treatment of patients with pulmonary tuberculosis, patients with a BMI < 17, totaling 19 samples , patients with a BMI between 17.0-18.4 totaling 25 samples , patients with a BMI between 18.25-25.0 totaled 143 samples, patients with a BMI of 25.1-27.0 totaling 12 samples , and patients with a BMI > 27, totaling 17 samples . There was differences between BMI before and after treatment in patients with pulmonary tuberculosis in BBKPM Surakarta p = 0.00. Conclusion: There was a significant difference in Body Mass Index before and after treatment in patients with pulmonary tuberculosis in BBKPM Surakarta p=0,00